Progress of Iron-Based Nanozymes for Antitumor Therapy - Sutrisno, Linawati; Hu, Yan; Hou, Yanhua; Cai, Kaiyong; Li, Menghuan; Luo, Zhong (Frontiers in Chemistry, 2020)
Artificial nanoscale enzyme-mimics (nanozymes) are promising functional alternatives to natural enzymes and have aroused great interest due to their inherent in vivo stability, affordability and high catalytic ability. Iron-based nanozymes are one of the most thoroughly investigated synthetic nanomaterials with versatile enzyme-like catalytic properties and demonstrated remarkable relevance to a variety of biomedical applications, especially the biocatalytic therapy against tumor indications. Nevertheless, despite the recent advances in biology and nanotechnology, the therapeutic performance of iron-based nanozymes in vivo is still limited by some technical issues such as low catalytic efficiency and lack of tumor specificity. In this mini review, we briefly summarized the representative studies of iron-based nanozymes, while special emphasis was placed on the current challenges and future directions regarding the therapeutic implementation of iron-based nanozymes for the development of advanced tumor therapies with improved availability and biosafety.